Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/ijerph17228403
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Capital and Burnout in Teachers: The Mediating Role of Flourishing

Abstract: In keeping with the growth in the development of healthy environments in organizational contexts, in recent years, there has also been increasing interest in the identification of personal psychological resources that contribute to improved worker mental health. From this proactive approach, this study examines the mediating role of flourishing in the relationship between psychological capital (PsyCap) and burnout in teachers, a professional group that is particularly prone to suffering from this syndrome. A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 71 publications
(95 reference statements)
3
36
0
2
Order By: Relevance
“…Moreover, it has been proposed as an indicator of well-being encompassing the experience of feeling joy, contentment, or happiness in life (i.e., hedonic well-being) as well as having an effective psychological functioning (i.e., eudaemonic well-being; Huppert and So, 2013). In fact, flourishing is related to less burnout and higher levels of health, life satisfaction, and work engagement (Garzón-Umerenkova et al, 2018;Younes and Alzahrani, 2018;Freire et al, 2020;Imran et al, 2020). Although this variable has not been extensively studied in adolescents (Witten et al, 2019), and even less in relation to academic performance, some studies suggest that higher levels of flourishing may contribute to a better academic performance and a greater likelihood of prioritizing academic chores (Datu, 2018;Datu et al, 2020).…”
Section: Flourishing As Mediatormentioning
confidence: 99%
“…Moreover, it has been proposed as an indicator of well-being encompassing the experience of feeling joy, contentment, or happiness in life (i.e., hedonic well-being) as well as having an effective psychological functioning (i.e., eudaemonic well-being; Huppert and So, 2013). In fact, flourishing is related to less burnout and higher levels of health, life satisfaction, and work engagement (Garzón-Umerenkova et al, 2018;Younes and Alzahrani, 2018;Freire et al, 2020;Imran et al, 2020). Although this variable has not been extensively studied in adolescents (Witten et al, 2019), and even less in relation to academic performance, some studies suggest that higher levels of flourishing may contribute to a better academic performance and a greater likelihood of prioritizing academic chores (Datu, 2018;Datu et al, 2020).…”
Section: Flourishing As Mediatormentioning
confidence: 99%
“…Psychological capital is the positive mental state shown by the individual in their process of growth and development and is a psychological resource that promotes individual growth and improvement. It mainly includes the four core elements of optimism, hope, resilience, and self-efficacy [23]. Some researchers have found that mindfulness can promote the accumulation of psychological capital [24,25], which can help to improve individual psychological capital [26,27].…”
Section: The Mediating Role Of Psychological Capitalmentioning
confidence: 99%
“…Numerous studies have confirmed that psychological capital and its interventions are related to reduced work-related problems, not to mention positive wellbeing and workrelated outcomes [96][97][98][99][100][101][102][103][104][105]. Research of the psychological capital in the public sector has evidenced its' numerous benefits [57,[106][107][108][109].…”
Section: Psychological Capitalmentioning
confidence: 99%
“…Fifth, numerous studies have reported links between psychological capital and wellbeing or life satisfaction [101,[150][151][152][153]. Some studies have reported links between positive organizational practices and wellbeing [18,19,91] or links between organizational practices and psychological capital [154].…”
Section: Importance Of the Studymentioning
confidence: 99%